Design of Monitoring System Distribution Water Based on IoT - Feras Ferdinan Sabono; Umi Yuliatin; Roni Heru Triyanto; Astrie Kusuma Dewi (Indonesian Journal of Energy and Mineral, 2022)
Based on the reference journal states that the increase in water use activities in urban areas for the lower Golan is 169.11 liters per person per day, and in the upper middle class it is 247.36 liters for each person per day, this cannot be denied that many activities use large amounts of water. large, so that from this problem, a distribution system and regular water monitoring is needed so that there is no wastage of water. In this research, a water distribution monitoring system has been designed, using Wemos D1 R1 and Blynk as interfaces. The purpose of this system design is to be able to design and realize a simple system for flow monitoring. This system consists of a water flow sensor YF-201 water flow sensor, Wemos D1 R1 Microcontroller, Blynk HMI to display measurement data that will detect the flow rate of water, then the water discharge value will be converted by Wemos D1 R1. After that Wemos D1 R1 will control and communicate with Blynk using the com port to display the measurement results in the form of numbers which are the final display of the flow rate measurement. For the experimental results of the prototype water distribution monitoring system tool, which is designed to show that the measurement system has been able to run quite well. accuracy 97.42 – 99.98%